Synthesis, characterization and biological evaluation of poly [LA-co-(Glc-alt-Lys)] for nerve regeneration scaffold - YIN, Yi-Xia; YI, Ji-Ling; XIE, Li-Juan; YAN, Qiong-Jiao; DAI, Hong-Lian; LI, Shi-Pu (Frontiers of materials science, 2014)
A novel nerve repairing material poly [LA-co-(Glc-alt-Lys)] (PLGL) was synthesized. The viability and growth of Schwann cells (SCs) co-cultured with poly (D, L-lactic acid) (PDLLA) films (control group) and PLGL films were evaluated by MTT assay and SEM observation. Then, contact angle measurement, histological assessment and enzyme-linked immunosorbent assay (ELISA) testing on inflammatory-related cytokines such as IL-10 and TGF-β1 were performed. The results showed that, compared with PDLLA, PLGL films possesses better hydrophilicity, biocompatibility, degradation property and less inflammatory reaction. The present study indicated that PLGL scaffolds would meet the requirements of artificial nerve scaffold and have a potential application in the fields of nerve regeneration.